A SOLO RESTAURANT KFT RENDEZVÉNYSZERVEZŐ TEVÉKENYSÉGE - RÁDULYNÉ DEÉ NIKOLETTA (2017)
I choose Solo Restaurants event organizational activities as my final thesis, because I spent my mandatory professional practice time at them. This way I could paticipate in events and gain real life experience in organizing them, not just learn about them in a theoretical way. This is why my thesis mostly consists of my own analysis, observation and research. I advised solutions to the problems and shortfalls through concrete examples. All of these regard, what changes would be necessary so that the company’s operation would change in a positive way. Solo Restaurants Kft’s restaurant has several positive attributes that distinguishes it from it’s competitors. The company’s responsibility is, that based on these attributes they put more emphasis on event organization. The thesis contains a through introduction of Solo Restaurants Kft, after the necessery theoretical summary. We will get to know the company’s structure, it’s functions, financial state, current partner relationships and the communicational tools they are using. A deep understanding of these attributes are necessary to correctly advise them. After this comes the grouping and detailed introduction of Solo Restaurant’s current event organizational function. In the next chapter there is the analysis of the competitors and their offerings based on the predetermined analytical aspects. This is of outstanding importance, since it creates the possibility of getting a competitive advantage over these other companies. I summarized the companie’s attributes in a SWOT analysis. I also did a primer research for event opportunities of the future. I also asked for feedback regarding these from the responders. I considered and built in these into my advices about the formation of the new event possibilities by analyzing my own research. In all my advices and remarks I sougth to bring valuable and tangible opportunities to Solo Restaurant Kft, which can be realized with their attributes and the financial state they are in.